Hypertension treatment goals; is it more than just a number?. Issue 11 (November 2017) - Zimmerman, Ethan; Moss, David
Abstract : N/A: Navar AM, Pencina MJ, Peterson ED. Assessing cardiovascular risk to guide hypertension diagnosis and treatment. JAMA Cardiol . 2016; 1(8):864–871.